Rapunzel Syndrome—An Extremely Rare Cause of Digestive Symptoms in Children: A Case Report and a Review of the Literature - Marginean, Cristina Oana; Melit, Lorena Elena; Sasaran, Maria Oana; Marginean, Razvan; Derzsi, Zoltan (Frontiers in Pediatrics, 2021)
Rapunzel syndrome is an extremely rare condition seen in adolescents or young females with psychiatric disorders consisting in a gastric trichobezoar with an extension within the small bowel. The delays in diagnosis are common since in its early stages is usually asymptomatic. We report the case of a 13-year-old girl admitted in our clinic for abdominal pain, anorexia and weight loss. The clinical exam pointed out diffuse alopecia, a palpable mass in the epigastric area, and abdominal tenderness at palpation, the patient weighing 32 kg. The laboratory tests showed anemia. The abdominal ultrasound showed a gastric intraluminal mass with a superior hyperechoic arc. The upper digestive endoscopy revealed a mass formed by hair, mucus and food occupying the gastric cavity with the extension into the duodenum confirming the diagnosis of Rapunzel syndrome. The giant trichobezoar of 511 grams, measuring 17x7x6.5 cm with a tail of approximately 3 cm, was successfully removed through laparotomy. Albeit rare, Rapunzel syndrome must never be forgotten as a differential diagnosis for digestive symptoms since its early detection hinders the occurrence of further complications.